(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2020)
The article discusses, the relative anatomical structure was investigated and micro- and macroelements from the ash coniferous leaves of Thuja occidentalis L. and Platycladus orientalis (L.) Franco have been revealed. First, the anatomical structure of the coniferous leaves of Thuja occidentalis L. and Platycladus orientalis (L.) Franco plants, which have been found at different points, were recorded using the Strasbourg-Fleming method, and the study was carried out according to the generally accepted method. Secondly, the composition of the leaves of Thuja occidentalis L. and Platycladus orientalis (L.) Franco plants collected from these points was tested by emission spectral analysis using an emission spectrometer connected to an Optima 8300 inductive plasma, the content of micro- and macroelements in liquid substances was determined with high accuracy by the method of determining the ash content. In the study of the anatomical structure, it has been found that the cross section of the coniferous leaf is abundant, stomata are anomocytic, resin cavities have been found on both sides of the central cylinder of Platycladus orientalis (L.) Franco. And when determining the ash content, the leaves of the species Thuja occidentalis L. and Platycladus orientalis (L.) Franco have showed a rich alkalinity of carbonates Ca, Fe, Mg. Trace elements Cu, Mn, Mo, Al, Li, Sr, W have been found in both species, however, Sn was not found in T. occidentalis, the results of the study have showed that the trace elements As, Cs, Ti, Nb, Zr, Ѕе are found in two species. Keywords: Thuja occidentalis L., Platycladus orientalis (L.) Franco, anatomical, ash content, micro- and macroelements.